Non-medical malpractice in public hospitals - Valdivia, José Miguel (Acta Bioethica, 2019)
Negligence is a key element of public hospitals’ responsibility under Chilean public law. When damages are provoked by non-medical misconducts, negligence is often shown under an unspecific face. This paper analyses the typical categories of this kind of liability, namely improper care (including failure to monitor patients), administrative dysfunctions, insufficient or defective devices. Judges normally look these cases as if they were ordinary administrative faults.